PREVALENCE AND SOURCES OF ACADEMIC STRESS AMONG UNDERGRADUATES IN KOGI STATE NIGERIA: A CROSS-SECTIONAL SURVEY - OLADIPE, TUNMISE (FUDMA Journal of Sciences, 2025)
Academic stress affects both psychological and physical health of Undergraduates. This study aimed to assess the prevalence of academic stress and identify various factors responsible for academic stress among undergraduates in Kogi State, Nigeria. The cross-sectional study was conducted among 134 randomly selected undergraduates from two Universities in the State. A self-administered questionnaire was used to collect data on the socio-economic, and academic stress score of all respondents. Descriptive and inferential statistics were employed to analyze the data. Using Rajendran and Kaliappan’s 40-item Academic stress scale, we found 97.8% (131/134) of respondents reported some level of stress (where (44.8% (60/134) were slightly stressed 44.8% (60/134) were moderately stressed) and 8.2% (11/134) were highly stressed and none reported extreme stress on the overall scale. Personal inadequacy, poor interpersonal Lecturer-students relationship and fear of failure were significantly associated with stress (one-way ANOVA, p<0.05), while fear of failure ranked highest (8%) among factors responsible for extreme academic stress. There were no significant (p> 0.05) association between academic stress and socio-demographic variables. Based on the findings it was concluded that there is a high prevalence of academic stress among undergraduates in Kogi State, and personal inadequacy, poor interpersonal relationships with Lecturers as well as fear of failure are the major factors responsible for stress amongst these students. It is therefore recommended that intervention strategies should be developed, which will enable students identify, individual sources of stress and address it through self-management and coping skills.